Time-motion analysis: non-elite Australian football - McManus, Alexandra; Stevenson, M.; Finch, C. (Sports Medicine Australia, 2005)
In Australian football players are ‘bigger, stronger, faster and more skillful’ than at any time in the games history. The interchange system had increased the pace of the game by maintaining a faster game tempo for longer periods of time. As a consequence of the changes to the game over time, injury rates have increased dramatically, as have the severity of injuries. To minimise the risk of injury, training regimes should simulate the demands placed on players during games. This presentation will outline a study of non-elite Australian footballers that quantified the positional demands placed in non-elite players during games. Players from one non-elite club based in Perth, Australia were followed during a pre-season and season. A total of 416 hours of video taped footage was analysed. On average, players changed movements every 10 seconds and completed approximately 600 separate movements during a games. The average distance travelled during a game ranged from 13 kilometres (fullback) to 17.4 kilometres (wing). The results indicated that there were significant differences between the positional demands during games however the training sessions observed did not reflect these differences. For example, the centreline players performed significantly more high intensity movements than other players therefore would need additional training drills to adapt to the higher energy demands required during a game. This presentation will outline the significant differences between the positional demands of Australian footballers and provide recommendations for training regimes that better reflect these demands.